2020
DOI: 10.3390/atmos11101133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Forest Fires on Regional Weather Conditions in Siberia

Abstract: Effects of forest fires on regional weather conditions were analyzed for Central and Eastern Siberia after warm and dry weather conditions in summer 2019 using COSMO-Ru (COnsortium for Small-scale MOdeling; Ru—Russia) and COSMO-RuART (ART—Aerosols and Reactive Trace gases) model systems. Four series of numerical experiments were conducted (one control experiment and three forest fire experiments assuming total vegetation destruction within the burned areas) to evaluate possible effects of forest fires on surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…This remote region is a part of a natural biosphere reserve and relatively untouched by human impact. We suggest that fires were caused by natural drivers, as temperature growth and increased frequencies of dry summer conditions were observed in Siberia during the last century (Groisman et al, 2007, 2012; Kirsanov et al, 2020). Tree ring studies and remote sensing observations in northern Siberia have shown that fire frequency and the area of fires increased significantly in the 20th century (Kharuk et al, 2011; Kirdyanov et al, 2020; Leskinen et al, 2020; Novenko et al, 2022).…”
Section: Discussionmentioning
confidence: 86%
“…This remote region is a part of a natural biosphere reserve and relatively untouched by human impact. We suggest that fires were caused by natural drivers, as temperature growth and increased frequencies of dry summer conditions were observed in Siberia during the last century (Groisman et al, 2007, 2012; Kirsanov et al, 2020). Tree ring studies and remote sensing observations in northern Siberia have shown that fire frequency and the area of fires increased significantly in the 20th century (Kharuk et al, 2011; Kirdyanov et al, 2020; Leskinen et al, 2020; Novenko et al, 2022).…”
Section: Discussionmentioning
confidence: 86%
“…As well as the effects on forest ecosystems, forest res can have signi cant economic and social consequences for local communities, and can be harmful or even fatal for humans living in the regions close to the burning areas (Kirsanov et al, 2020;Ntinopoulos et al, 2022). Although it is not comprehensively investigated, the effects of forest res in Namibia have severely affected economic, social, and environmental spheres in recent years.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…The effects include disturbance of wildlife habitat, acceleration of nutrient cycling, and mortality of individual trees (Dale et al, 2001;Hutchinson et al, 2019;Jhariya and Raj, 2014). Additionally, forest res can reduce precipitation by releasing substantial amounts of smoke into the atmosphere, thus promoting more drought and res (Kirsanov et al, 2020). Consequently, the precipitation regime signi cantly impacts the number of res and areas burned (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the different environmental factors influencing fire activity in Central Siberia, the spatial distribution of permafrost must be also considered. The study areas are underlain by continuous, discontinuous, or isolated permafrost that can influence the spatial vegetation distribution and surface moisture conditions either directly or indirectly, and they can in turn impact forest fire spatial patterns and severity [18]. At the same time, forest fires can also be an important driver of permafrost thaw that can intensify the emission of GHG into the atmosphere and accelerate global warming [7].…”
Section: History Of Wildfires In North-central Siberia Regionsmentioning
confidence: 99%
“…They also result in large emissions of greenhouse gases (GHG) and aerosols into the atmosphere [16,17]. All of these factors affect surface air temperature, cloud formation, and precipitation [18].…”
Section: Introductionmentioning
confidence: 99%